EPEN-04. SIOP EPENDYMOMA I: FINAL RESULTS, LONG TERM FOLLOW-UP AND MOLECULAR ANALYSIS OF THE TRIAL COHORT: A BIOMECA CONSORTIUM STUDY. (1st June 2021) - A. Ritzmann, Timothy; Chapman, Rebecca J; Macarthur, Donald; Mallucci, Conor; Kilday, John-Paul; Thorp, Nicola; Modena, Piergiorgio; Giagnacovo, Marzia; Dineen, Rob; Jaspan, Timothy; Pajtler, Kristian W; Jacques, Thomas S; et al.
Abstract: Introduction: Surgery and radiotherapy are established childhood ependymoma treatments. The efficacy of chemotherapy has been debated. We report final results of the SIOP Ependymoma I trial, with 12-year follow-up, in the context of a post-hoc analysis of more recently described biomarkers. Aims and Methods: The trial assessed event free (EFS) and overall survival (OS) of patients aged three to 21 years with non-metastatic intracranial ependymoma, treated with a staged management strategy targeting maximum local control. The study also assessed: the response rate (RR) of subtotally resected (STR) disease to vincristine, etoposide and cyclophosphamide (VEC); and surgical operability. Children with gross total resection (GTR) received radiotherapy of 54 Gy in 30 daily fractions over six weeks, whilst those with STR received VEC before radiotherapy. We retrospectively assessed methylation and 1q status alongside hTERT, RELA, Tenascin C, H3K27me3 and pAKT expression. Results: Between 1999 and 2007, 89 participants were enrolled, 15 were excluded with metastatic (n=4) or non-ependymoma tumours (n=11) leaving a final cohort of 74. Five- and ten-year EFS was 49.5% and 46.7%, OS was 69.3% and 60.5%. 1q gain was associated with poorer EFS (p=0.002, HR=3.00, 95%CI 1.49–6.10). hTERT expression was associated with worse five-year EFS (20.0% Vs 83.3%, p=0.014, HR=5.8). GTR was achieved in 33/74 (44.6%) and associated with improved EFS (p=0.006, HR=2.81, 95% confidence interval 1.35–5.84). There was an improvement in GTR rates in the latter half of the trial (1999-2002 32.4% versus 2003-2007 56.8%). Despite the protocol, 12 participants with STR did not receive chemotherapy. However, chemotherapy RR was 65.5% (19/29, 95%CI 45.7–82.1). Conclusions: VEC exceeded the pre-specified RR of 45% in children over three years with STR intracranial ependymoma. However, cases of inaccurate stratification at treating centres highlights the need for rapid central review. We also confirmed associations between 1q gain, hTERT expression and outcome.